Pembuatan Pembangkit Listrik Termoelektrik pada Kompor Berbahan Bakar Pellet Biomassa Kayu Karet - Devanka Arya Levin; Jonatan Sinurat; Anak Agung Ngurah Amrita; Ida Bagus Gede Manuaba (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Biomass is one of the materials that can be utilized as fuel. To ensure optimal quality, effective management of biomass is required to maximize its potential. One possible approach is the application of a biomass stove fueled by rubber wood pellets. By integrating a thermoelectric generator, data can be obtained to determine whether all aspects meet the established standards. This system is designed to generate electrical energy from combustion heat, supported by components such as a buck-boost converter and a 3V DC lamp. Testing was carried out using proximate and ultimate analyses on the fuel as well as the Water Boiling Test (WBT) on the stove, referring to SNI 8021:2020 and SNI 8021:2014 standards. The results showed that rubber wood pellets contained 7.64% moisture and had a calorific value of 4050 kcal/kg. The stove demonstrated an efficiency of 23.53%–37.28% and a fuel consumption rate of 0.61–0.77 kg/hour, both of which meet the requirements. In addition, the thermoelectric generator produced a voltage of 3.6 V and an electric current of 0.05 A, which are higher than those reported in previous studies (2.06 V and 0.01 A, respectively). Therefore, this thermoelectric biomass stove system is considered successful and feasible for further development as an alternative energy application.